Kepemimpinan Profetik: Telaah Kepemimpinan Khulafa` Al-Rashidin - Roni Harsoyo (STAI Ihyaul Ulum Gresik, 2020)
The success of Khulafa` al-Rashidin with all his leadership is loaded with wisdom that can be learned for all fields of human life at any time. The prophetic leadership values ​​carried out by the caliphs inspire the present leaders to always carry out their leadership, in order to be able to deliver their organizations to achieve their stated vision, mission and goals. This article aims to describe the values ​​of prophetic leadership that have been undertaken by Khulafā` al-Rashidīn. The search results show that the prophetic values ​​of Khulafā` al-Rashidīn that can be developed in educational leadership are: 1) Firmness; 2) Courage; 3) Generosity; 4) Justice; 5) Authority; 6) ‘Abqari (strong); 7) Decisive, trustworthy and responsible; 8) Implement justice; 9) High affection; 10) Amar ma'ruf nahi munkar; 11) Emphasizing the righteous aqeedah and sincerity in worship; 12) Give a good example of moral character; 13) Openness in self-development of subordinates; 14) Unite; 15) Give the right to the People to correct the leadership; 16) Carrying out deliberations in his leadership; 17) Upholding justice and equality; 18) Paying attention to other people's conditions in daily life; 19) Implement freedom; 20) Democracy; 21) Charismatic; 22) Millitary; 23) Courageous; and 24) Smart.